WOMAN ENTREPRENEURIAL LEADERSHIP: KEPEMIMPINAN PEREMPUAN SEBAGAI UPAYA PENGEMBANGAN JIWA ENTREPRENEURSHIP ANAK USIA DINI - wahidah, Finadatul; Kurnia, Rahmi; Lailisna, Novi Nur (EGALITA, 2023)
Entrepreneurship departs from the concept of human independence in solving the problems at hand. In entrepreneurship, humans try to get out of life's problems. They turn uncertainty into promising opportunities. The human ability to turn challenges into economic opportunities has existed since their existence in the world. They live, develop and progress on the principle of independence. Every effort was made to meet the needs of his life. This study was carried out by RA Ulul Albab, located at Bumi Mangli Permai Jember. Women's leadership at RA Ulul Albab has gotten awards and has innovations in developing an entrepreneurial spirit in early childhood. The application of AUD's entrepreneurial spirit will not be separated from the role of the leader. This study uses a qualitative approach; the technique used in selecting informants is purposive. This means determining informants according to selected criteria relevant to the research problem. Data collection techniques using observation, interviews and documentation. Data analysis followed the method Milles and Huberman proposed: data condensation, data presentation, drawing conclusions or verification. The validity of the data used source triangulation and technical triangulation. The focus of the research is 1) How does women's leadership make the innovations in developing the entrepreneurial spirit of Early Childhood?; 2) How is the leadership behaviour of women in developing the entrepreneurial spirit of Early Childhood? The results of the research are 1) The innovation carried out by the principal of RA Ulul Albab in developing the entrepreneurial spirit of Early Childhood is carried out in two steps, namely: a) Thinking New Thing; b) Doing New Things; 2) Management by Exception-Active, a figure who is active and firm in paying attention to the implementation of the duties of teachers so as not to make mistakes or failures. Supervising leaders who always supervise and motivate teachers and Management by Self-protective-spiritual, leaders who have more orientations based on brotherly relationships and low levels of selfishness, leaders who are inspirational visionary, and prioritize Collaborative team orientation, honest leaders and trust.